ДІЯЛЬНІСТЬ АНГЛІЙСЬКОЇ ДИПЛОМАТІЇ ПІД ЧАС ЗАГОСТРЕННЯ ПОЛЬСЬКОГО ПИТАННЯ У 1863 РОЦІ (Zaporizhzhia Historical Review, 2021)
The article is devoted to the investigation of the activity of British diplomacy during the rising of Polish question in 1863 year. The policy of Great Britain in this conflict, the complex international atmosphere in Europe of that time, was analyzed in details. The author came to the conclusion that the main aim of British diplomacy in the conflict was to use it so that two main rivals of Great Britain France and Russia were weakened and their alliance was destroyed. The government of lord Palmerston achieved this aim, but Great Britain suffered diplomatic defeat in the conflict and spoiled own relations with France.